2016
DOI: 10.1128/jb.00848-15
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the Process of Nucleoid Exclusion of Protein Aggregates in Escherichia coli

Abstract: Escherichia coli segregates protein aggregates to the poles by nucleoid exclusion. Combined with cell divisions, this generates heterogeneous aggregate distributions in subsequent cell generations. We studied the robustness of this process with differing medium richness and antibiotics stress, which affect nucleoid size, using multimodal, time-lapse microscopy of live cells expressing both a fluorescently tagged chaperone (IbpA), which identifies in vivo the location of aggregates, and HupA-mCherry, a fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…Local concentrations may be higher or lower in some cell regions depending on: (i) sites of production and degradation; (ii) diffusion; (iii) kinetics of association and dissociation with cellular structures, e.g. nucleus, cell membrane or cytoskeleton; and (iv) attraction to or exclusion from cell regions (Neeli-Venkata et al, 2016; Mondal et al, 2011). With this in mind, colocalization, anti-colocalization and non-colocalization should be considered as the relationship in the local concentrations of two types of molecules, which may be due to many factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local concentrations may be higher or lower in some cell regions depending on: (i) sites of production and degradation; (ii) diffusion; (iii) kinetics of association and dissociation with cellular structures, e.g. nucleus, cell membrane or cytoskeleton; and (iv) attraction to or exclusion from cell regions (Neeli-Venkata et al, 2016; Mondal et al, 2011). With this in mind, colocalization, anti-colocalization and non-colocalization should be considered as the relationship in the local concentrations of two types of molecules, which may be due to many factors.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to common sites of production, action, binding, or degradation. Anti-colocalization indicates two molecules have high concentrations in different cell regions and thus at least one mechanism is causing the molecules to be recruited to and/or exclude from different regions, one molecule excludes the other from a region (Bakshi et al, 2015; Neeli-Venkata et al, 2016) or the molecules eliminate each other in the same location, e.g. when non-coding RNAs binding to mRNAs both are destroyed (De Lay et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…There are claims that transport of aggregates to the poles is energy-driven as studies on reassembly of pressure dissociated IBs revealed that confinement to the pole is caused by the presence of the nucleoid but reassembly of smaller aggregates into large IBs does not occur in energy and nutrient depleted cells [16]. However, there are also reports stating that exclusion of aggregates from mid-cell to the pole is energy-free, and simply results from nucleoid exclusion [17,20,[28][29][30]. Restriction of aggregates to the pole was also observed during treatment with substances disrupting the protein motive force, suggesting an energy independent process of aggregation [20].…”
Section: Cellular Formation Of Ibsmentioning
confidence: 98%
“…It may also suggest common sites of production, action, or degradation. Negative correlation may suggest a physical or biochemical mechanism that sequesters red and green species from each other [ 1 , 2 ]. A number of different procedures for assessing co-localization between two images are described in a recent review [ 3 ].…”
Section: Introductionmentioning
confidence: 99%